PENGARUH INOVASI PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN MELALUI LOYALITAS PELANGGAN DI PT PEGADAIAN KOTA MADIUN PROVINSI JAWA TIMUR - Amongraga, Satria (Prodi Magister Manajemen Universitas Wijaya Putra, 2025)
This study aims to analyze the impact of product innovation, brand image, and customer loyalty on the purchase decisions of customers at PT Pegadaian Kota Madiun. Product innovation and brand image are considered important factors influencing customer loyalty, which in turn affects purchase decisions. Data was collected through a survey of PT Pegadaian Kota Madiun customers using a questionnaire that has been tested for validity and reliability. Data analysis was conducted using path analysis to test the relationships between variables. The results indicate that product innovation has a positive and significant effect on customer loyalty. Brand image also has a positive and significant effect on customer loyalty. Customer loyalty, as an intervening variable, shows a positive and significant effect on purchase decisions. Product innovation and brand image also directly affect purchase decisions. These findings indicate that product innovation and brand image not only directly influence purchase decisions but also affect them through customer loyalty as an intervening variable. The practical implication of this research is that PT Pegadaian should continue to focus on product innovation and strengthening brand image to enhance customer loyalty and purchase decisions. This strategy can help the company retain existing customers and attract new ones, ultimately improving overall business performance.